Developing fencing policies for dryland ecosystems. Issue 3 (20th April 2015) - Durant, Sarah M.; Becker, Matthew S.; Creel, Scott; Bashir, Sultana; Dickman, Amy J.; Beudels‐Jamar, Roseline C.; Lichtenfeld, Laly; Hilborn, Ray; Wall, Jake; Wittemyer, George; Badamjav, Lkhagvasuren; Blake, Stephen; et al.
Summary In dryland ecosystems, mobility is essential for both wildlife and people to access unpredictable and spatially heterogeneous resources, particularly in the face of climate change. Fences can prevent connectivity vital for this mobility. There are recent calls for large‐scale barrier fencing interventions to address human–wildlife conflict and illegal resource extraction. Fencing has costs and benefits to people and wildlife. However, the evidence available for facilitating sound decision‐making for fencing initiatives is limited, particularly for drylands. We identify six research areas that are key to informing evaluations of fencing initiatives: economics, edge permeability, reserve design, connectivity, ecosystem services and communities. Policy implications. Implementing this research agenda to evaluate fencing interventions in dryland ecosystems will enable better management and policy decisions. The United Nations Conventions on Migratory Species (CMS) and to Combat Desertification (UNCCD) are appropriate international agreements for moving this agenda forward and leading the development of policies and guidelines on fencing in drylands.